« Never was there a happier partnership » : les illustrations d’Arthur Hughes pour At the Back of the North Wind de George MacDonald - Catherine Persyn (Cahiers Victoriens et Edouardiens)
George MacDonald and his illustrator and friend the Pre-Raphaelite Arthur Hughes were kindred spirits, whose affinities appear nowhere better than in At the Back of the North Wind, the happiest of many happy collaborations between the two men. The present paper—in which a good number of Hughes’s seventy-six designs for MacDonald’s best-seller are examined—is built around three main lines. A Subject After His Own Heart shows how congenial the subject-matter was to Hughes, and how likely to elicit the best from him as illustrator. A reference to the unsuspected depths of the so-called children’s book, Where More is Meant Than Meets the Ear/Eye endeavours to highlight the subtlety of Hughes’s reading of the text and the efficacy of his choices. Last but not least, the eponymous character of the story and mouthpiece of the author’s philosophical views, the magical North Wind, whose sole mention immediately calls to mind the most inspired and best-known engravings of the whole series, deserved to be studied at some length, which is done under the heading : You Cannot Barre Love Oute.